Discoveries in the ruins of Nineveh and Babylon : with travels in Armenia, Kurdistan and the desert : being the result of a second expedition undertaken for the trustees of the British Museum - Layard, Austen Henry, 1817-1894. (New Jersey)
xxiii, 686, [7] sayfa